Quintessence dissipative superattractor cosmology - Chimento, Luis Pascual (2001)
We investigate the simplest quintessence dissipative dark matter attractor cosmology characterized by a constant quintessence baryotropic index and a power--law expansion. We show a class of accelerated coincidence--solving attractor solutions converging to this asymptotic behavior. Despite its simplicity, such a ``superattractor´´ regime provides a model of the recent universe that also exhibits an excellent fit to supernovae luminosity observations and no age conflict. Our best fit gives $alpha=1.71pm 0.29$ for the power-law exponent. We calculate for this regime the evolution of density and entropy perturbations.